Stress and emotion regulation with graphic activities and expressive narrative - Vanegas-Farfano, Minerva (2016)
The present study evaluated instructions in graphic and expressive writing tasks as stress and emotion regulation activity aids. Six experimental groups were composed of thirty university students. Effects were measured with the Mexican versions of the Perceived Stress Scale (PSS) and the Positive and Negative Affect Schedule (PANAS). The groups were similar in  the perceived stress and affect measures in time 1. Results demonstrated positive changes in both variables in time 2,for the intervention groups. The results indicate that it is necessary to evaluate the types of instructions given in experimental and clinical settings.